Bridging the gap between biomechanics and artificial intelligence - Bacic, B. (ISBS - Conference Proceedings Archive (Konstanz), 2006)
In contrast to widely researched areas of convergence such as between Artificial Intelligence (AI) and medicine there is minimal evidence of AI in biomechanics for sports. The main focus of this paper is the development of AI coaching systems with a high degree of autonomy that can discover new knowledge from data. This paper relates to areas of AI, biomechanical data, and qualitative analysis of human movement. It first provides an overall rationale for possible AI implementations then reports machine learning related findings from AI golf coaching software and a tennis coaching prototype. A point of view, presented as a scope, is that the future role of AI in sport coaching is about automation, knowledge discovery and enhanced human-like interaction.